RELATIONSHIP OF IMMUNOHISTOCHEMICAL EXPRESSION OF MISMATCH REPAIR GENE PRODUCTS AND CLINICOPATHOLOGICAL FEATURES IN PATIENTS WITH LOW-GRADE ENDOMETRIAL CANCER - Joksimovic, Marija; Jankulovski, Nikola; Petrusevska, Gordana; Jankovska, Biljana Ognenoska; Ivanovska, Beti Zafirova; Stojcevski, Saso; Aluloski, Igor; Tanturovski, Mile; Joksimovic, Vladimir (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Background: This study examines the relationship between mismatch repair (MMR) gene expression and clinicopathological features in patients with low-grade endometrial cancer (EC).  Methods: A prospective cohort of 40 patients with histologically confirmed low-grade EC underwent immunohistochemical analysis to determine MMR status. Clinical data, including age, body mass index (BMI), menopausal status, parity, and comorbidities, were collected. Histopathological evaluations assessed myometrial invasion,lymphovascular invasion and disease stage.  Results: MMR deficiency (MMRd) was identified in 35% of patients, predominantly associated with MLH1/PMS2 loss. No significant associations were found between MMR status and clinical characteristics such as age, BMI, or comorbidities. However, MMRd tumors exhibited a significantly higher prevalence of myometrial invasion over 50% (85.71% vs. 38.46%, p=0.0042) and lymphovascular invasion (71.43% vs. 19.23%, p=0.00114). Additionally, MMRd cases were more frequently associated with advanced disease stages, particularly in stage IIIC (28.57% vs. 7.69%, p=0.078).  Conclusion: The importance of MMR status in the biological behavior of low-grade endometrial cancer is highlighted in this study. The strong correlation between MMR deficiency and aggressive histopathological features such as increased myometrial and lymphovascular invasion, highlights the need to integrate MMR testing into clinical practice, even if clinical parameters showed no significant association with MMR expression. These results suggest that MMRd may be a useful prognostic indicator that requires more research to improve patient outcomes and treatment approaches for low-grade endometrial cancer.  Keywords : endometrial cancer, low grade, mismatch repair